A Multistate Trial of an Early Surveillance Program for Autism Within General Practices in Australia - Barbaro, Josephine; Masi, Anne; Gilbert, Melissa; Nair, Radhika; Abdullahi, Ifrah; Descallar, Joseph; Dissanayake, Cheryl; Eastwood, John; Hasan, Iqbal; Jalaludin, Bin; Karlov, Lisa; Khan, Feroza; et al. (Frontiers in Pediatrics, 2021)
Background: The early detection of developmental conditions such as autism is vital to ensure children can access appropriate and timely evidence-based supports, services, and interventions. Children who have undetected developmental conditions early in life are more likely to develop later health, developmental, learning, and behavioral issues, which in turn can have a cumulative effect over the life course. Methods: The current protocol describes a multi-site, cluster randomized control trial comparing a developmental surveillance pathway for autism to usual care, using opportunistic visits to general practitioners (GP). Units of randomization are GP clinics across two Australian states (New South Wales and Victoria), with thirty clinics within each state, each of which will aim to recruit approximately forty children aged between approximately eighteen- and twenty-four-months, for a total of ~2,400 participants. Children will be randomized to two clusters; namely, an autism surveillance pathway (ASP) or surveillance as usual (SaU). The screening process for the ASP arm involves primary and secondary screenings for developmental concerns for autism, using both parent and GP reports and observations. Children in both arms who show signs of developmental concerns for autism will be offered a full developmental assessment by the research team at twenty-four months of age to determine the efficacy of developmental surveillance in successfully identifying children with autism. The trial is registered with ANZCTR (ACTRN12619001200178) and reporting of the trial results will be according to recommendations in the CONSORT Statement.